Evolution of individuation of group ranches in Masailand - Pasha, I.K.O. (Winrock International, 1986)
Analysis factors that have led to the evolution of individuation of group ranches in Masailand, Kenya. Reviews the Development of the group-ranch concept and achievements and failures of the group-ranch program.